Adolescent’s Subjective Well-being With A Military Family Background - Maria Ndouk; Apris Adu; Juliana Benu (Journal of Health and Behavioral Science, 2021)
Adolescence is a time with various opportunities of conflict. Conflict could be happen if adolescents have a different value of life with adult as parents, siblings, or society. Conflict that allowed to happen might be ensued an identity disorder, mental illness, and issue of quality of life. Adolescents’ quality of life related with subjective well-being. Subjective well-being is an individual’s subjective evaluations about him/her whole life. The aim of this research was described adolescents’ subjective well-being with a military family background in koramil dormitory. Participants of this research were three adolescents. Research methodology that used was qualitative with data collection techniques were semi-structure interview and un-structure observation. The results of research discovery that three participants were achieve their life satisfaction especially by their domain life satisfaction as family, peer group-community and education achievement. Furthermore participants have experienced many positive emotion, and lack of negative emotion in their presence life too.